Scarce occurrence and high threat of the Peruvian Plantcutter, Phytotoma raimondii - Romo, Mónica (2015)
In this article, we present an update on the conservation statuts of the Peruvian Plantcutter. We find little presence of the species within its distribution area we catalog threats to the remaining populations. From Tumbes to Ancash only six sites have been identified with populations of more than 10 individuals and only three sites where the species is known to reproduce. Results indicate that the current total population is less than 500 individuals. These sites where the species is found contain floral species typical of the Peruvian desert scrub, several of which are threatened. Sites are very small (between 5 to 150 ha), highly fragmented and are under immediate threat of destruction due to agriculture, urban expansion, illegal logging, livestock foraging, and the introduction of exotic plant species.